2012
DOI: 10.1002/ldr.2181
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Driven Land Degradation: Consequences for Plant Diversity and Soil in Arid Subtropical Thicket in South-Eastern Africa

Abstract: Investigations were made of plant and soil responses to severe degradation through heavy grazing and browsing in arid, succulent, subtropical thicket. Severe degradation of thicket is of major concern in terms of threatened biodiversity, unsustainable utilization and collapse of other ecosystem services. We used a natural, field contrast, case‐study approach, sampling within plots under lightly and heavily stocked conditions. Mean plant species diversity and richness did not change significantly at sample plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 64 publications
(128 reference statements)
1
23
1
Order By: Relevance
“…Some reports of short duration grazing followed by long periods of pasture rest have shown increases in SOC, reduced soil compaction and the risk of erosion even within relatively short periods (<5 years; Sanjari et al, 2008;Teague et al, 2011;McSherry & Ritchie, 2013). While there is general agreement in the literature which shows a negative impact of increasing agricultural intensity on biodiversity (Lunt et al, 2007;Díaz et al, 2007;Rutherford et al, 2012), the impact of rangeland grazing intensity on diversity is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports of short duration grazing followed by long periods of pasture rest have shown increases in SOC, reduced soil compaction and the risk of erosion even within relatively short periods (<5 years; Sanjari et al, 2008;Teague et al, 2011;McSherry & Ritchie, 2013). While there is general agreement in the literature which shows a negative impact of increasing agricultural intensity on biodiversity (Lunt et al, 2007;Díaz et al, 2007;Rutherford et al, 2012), the impact of rangeland grazing intensity on diversity is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…In grasslands throughout the world, grazing by domestic livestock is often associated with a certain degree of changes in species composition and soil degradation (Milton et al, 1994;Busso, 1997;Cerdà & Lavée, 1999;Angassa, 2012;Rutherford et al, 2012;Mekuria & Aynekulu, 2013;Romina et al, 2014). Selective herbivory of the more desirable species appears to be the dominant mechanism in the processes of species replacement (Anderson & Briske, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Land degradation, caused by overgrazing and other inappropriate land uses, has been recognized as one of the major threats to ecosystem services and functioning on perennial grasslands worldwide, especially in arid or semi-arid ecosystems (Bai et al, 2007;Ford et al, 2012;Liu et al, 2012;Rutherford et al, 2012). Subjected to a considerable population pressure, grasslands in China are much susceptible to land degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced cation binding causes less cation uptake and use by the plant which causes increased cation availability in the soil due to cations not being used (Oertli 2008). Elevated cations were also reported by Rutherford, Powrie & Husted (2014) in comparing heavily browsed sites with low above-ground vegetative biomass to less browsed sites with higher biomass. They suggested that it might have been a result of nutrient enrichment from livestock urine and dung.…”
Section: Discussionmentioning
confidence: 67%